La littérature populaire du Kailyard, substrat nécessaire à la Renaissance écossaise - Jean Berton (Cahiers Victoriens et Edouardiens)
This study on the popular literary movement of the Kailyard aims to show that it was a necessary step to launch the Scottish Renaissance in the twentieth century. It concentrates on the founding trilogy of The Bonnie Briar Bush by Iain Maclaren, Auld Licht Idylls by James Barrie and The Stickit Minister by Samuel Crockett. It briefly explores the characteristics of the Kailyard before suggesting ten items belonging to the genre. After examining the main trend in the criticism of the Kailyard, it has been decided to bypass the usual English point of view so as to better appreciate the ironical tone of those texts deserving a study of what they are rather than what they should be. Neo-contextualism is a fruitful approach as it enables us to highlight the link between the Kailyard and the preceding Glasgow Boys movement. With the benefit of hindsight we can see that the Kailyard movement stands on a strong position between Walter Scott’s novels and the fiction of the end of the Scottish Renaissance.